2017
DOI: 10.1186/s11671-017-2377-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel Bi4Ti3O12/Ag3PO4 heterojunction photocatalyst with enhanced photocatalytic performance

Abstract: In this work, we integrated Ag3PO4 with Bi4Ti3O12 to form Bi4Ti3O12/Ag3PO4 heterojunction nanocomposites by an ion-exchange method. The as-prepared Bi4Ti3O12/Ag3PO4 composites were systematically characterized by means of XRD, SEM, TEM, BET, XPS, UV-vis DRS, EIS, PL spectroscopy, and photocurrent response. SEM, TEM, and XPS results demonstrate the creation of Bi4Ti3O12/Ag3PO4 heterojunction with obvious interfacial interaction between Bi4Ti3O12 and Ag3PO4. PL spectra, EIS spectra, and photocurrent responses re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(46 citation statements)
references
References 62 publications
1
45
0
Order By: Relevance
“…It is well known that the photogenerated holes in the VB of g-C 3 N 4 possess strong ability to oxidize dyes directly. However, because the VB potential of g-C 3 N 4 is negative to the redox potentials of H 2 (5)). The analysis result confirms the role of H 2 O 2 for the dye degradation.…”
Section: Photocatalytic Mechanismmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well known that the photogenerated holes in the VB of g-C 3 N 4 possess strong ability to oxidize dyes directly. However, because the VB potential of g-C 3 N 4 is negative to the redox potentials of H 2 (5)). The analysis result confirms the role of H 2 O 2 for the dye degradation.…”
Section: Photocatalytic Mechanismmentioning
confidence: 99%
“…(1) (2) In the above equation, the X and E e are the absolute electronegativity of materials (defined as the arithmetic mean of the electron affinity and the first ionization of the constituent atoms) and energy of free electrons on the hydrogen scale (~ 4.5 eV), respectively. The X value of BiFeO 3 is calculated to be 5.93 eV based on the data reported in literatures 34,35 , and the X value for g-C 3 N 4 nanoparticles is reported to be 4.72 eV 36 .…”
Section: Optical Absorption Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, owing to its appropriate energy band position and narrow bandgap, Ag 3 PO 4 is widely employed as the cocatalyst to combine with other photocatalysts to form composites, leading to an obvious improvement of photocatalytic behavior, such as Ag 3 PO 4 /Bi 2 WO 6 , Ag 3 PO 4 /BiPO 4 , Ag 3 PO 4 /Bi 2 O 2 CO 3 , Ag 3 PO 4 /g-C 3 N 4 , Ag 3 PO 4 /BiVO 4 , Bi 4 Ti 3 O 12 /Ag 3 PO 4 , Ag 3 PO 4 /ZnFe 2 O 4 , Ag 3 PO 4 /WO 3 , Ag 3 PO 4 /ZnO, and Bi 2 MoO 6 /Ag 3 PO 4 [3847]. It is reported that BiFeO 3 is an n-type semiconductor and Ag 3 PO 4 is known as a p-type semiconductor [43, 48]. The construction of Ag 3 PO 4 /BiFeO 3 p-n heterojunction composites may be a feasible method to obtain efficient photocatalyst.…”
Section: Introductionmentioning
confidence: 99%